Desert as therapeutic space: Cultural interpretation of embodied experience in sand therapy in Xinjiang, China. (September 2018) - Wang, Ke; Cui, Qingming; Xu, Honggang
Abstract: The existing research on therapeutic landscapes reveals more positive and pleasant experiences generated in blue and green spaces and their effects on health. This study draws on a case study of sand therapy at Turpan City in China in order to explore in the 'yellow' space of the desert how painful embodied experiences and cultural beliefs are assembled to produce therapeutic experiences. The results show that the sand therapy participants sought painful haptic sensations such as burning, heat and sweating by touching hot sand as treatment. Individuals interpreted these painful bodily sensations through health-related cultural beliefs of yin - yang balance and Qi to generate particular therapeutic experiences. This study suggests the researchers to be more attentive to painful therapeutic landscapes. Highlights: The yellow space of desert can be constructed as therapeutic space. Bodily experiences are crucial for people to obtain subjective therapeutic experiences. The therapeutic experiences in the desert are the outcomes of an intersection between embodied experiences and cultural constructions.